Inspection of defect at a two floor house in Jalan Kg. Raja, Pagoh, Mukim Jorak, Muar, Johor - Salim, Salman; Mohamad Azali, Fatin Farhawanie; Ruslan, Fatin Najihah; Naim, Fitri; Mohd Jaaffar, Khairunnisa (Penerbit UTHM, 2020)
A defect is a building flaw or design mistake that reduces the value of the building and causes a dangerous condition. A construction defect can arise due to many factors such as poor workmanship or the use of inferior materials. Defective building construction not only contributes to the final cost of the product but also to the cost of maintenance, which can be substantial...